M17 The effect of multidisciplinary therapy on objective and subjective sleep quality in premanifest huntington's disease. (13th September 2016) - Bartlett, Danielle; Cruickshank, Travis; Lazar, Alpar; Lampit, Amit; Slater, James; Rankin, Tim; Hoult, Linda; Pulverenti, Tim; Govus, Andrew; Power, Brian; Reyes, Alvaro; Newton, Rob; et al.
Abstract : Background: Subjective and objective sleep disturbances have been reported in premanifest Huntington's disease (pre-HD). These disturbances have the potential to induce structural and functional changes to the brain, including cognitive deficits, and may facilitate, or even contribute to, disease onset and progression. Treatment of sleep disturbances could therefore improve function in affected individuals. Here, we investigated the effects of a non-pharmaceutical, short duration multidisciplinary therapy intervention on subjective and objective sleep in pre-HD participants. Aims: To evaluate the effects of multidisciplinary therapy on sleep patterns and subjective sleep quality in pre-HD participants. Methods: Eleven pre-HD participants aged 40 ± 11 years (5 male) underwent a twelve week multidisciplinary therapy intervention consisting of three, two hour sessions per week encompassing supervised group exercise and cognitive training. Objective (actigraphy) and subjective (Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale, Consensus Sleep Diary) measures of sleep were obtained at baseline, six weeks and twelve weeks. Stress, depression and anxiety were measured at each time-point using the Perceived Stress Scale and the Hospital Anxiety and Depression Scale (as potential confounders of sleep abnormalities). Results: All participants completed the required number of therapy sessions (30 sessions in total) for the study. Decreases, relative to baseline, in sleep onset latency (d > 0.5) and number and duration of awakenings (d > 0.2) were observed following the 12 week intervention. Subjective sleep quality also improved following 12 weeks of physical and cognitive training (d > 0.5). Conclusion: This study provides evidence that multidisciplinary therapy has the potential to improve subjective and objective sleep quality in pre-HD. It is possible that a longer intervention duration may further improve sleep quality outcomes in this population.